Interviews with David Lee, February 15, 1997; June 19, 1999; July 15, 2000; November 16, 2002 - Lee, David I. (Valdosta State University Archives and Special Collections, 1997)
Oral history interview(s) with David Irwin Lee, Hoboken (Ga.), February 15, 1997; June 19, 1999; July 15, 2000; November 16, 2002. Fieldworker: Laurie Kay Sommers. Audio files digitized from DAT or cassette tape. Part of the Sacred Harp Series: South Georgia Folklife Project at Valdosta State University Archives and Special Collections. Includes following interviews: CAS-1004.06: Interview with David Lee and Clarke Lee, Hoboken (Ga.), February 15, 1997. 01:59:50. Includes transcript. Home of David and Cathy Lee. DAT-1004.26: Interview with David I. Lee, Hoboken (Ga.), June 19, 1999. No transcript. A recording of the monthly Sacred Harp Singing at Hoboken Elementary School. This sing uses the B.F. Cooper Revised Edition of the Sacred Harp. DAT-1004.34: Interview with David I. Lee for Pulse of the Planet, Hoboken (Ga.), July 15, 2000. 00:49:43. Includes partial transcript. Interview about Sacred Harp With David Lee recorded for The Pulse of the Planet Radio Show. DAT-1004.48: Interview with David I. Lee, Hoboken (Ga.), November 16, 2002. 00:44:20. No transcript.
Interview with David Lee and Clarke Lee, Hoboken (Ga.), February 15, 1997
Interview with David I. Lee, Hoboken (Ga.), June 19, 1999.
4 electronic record(s) and derivatives. 4 audio file(s) (wav, mp3) 3.15 GB (3,390,593,382 bytes). 8 PDF documents (36 scans, jp2). Bag approx. 4.14 GB (4,456,028,882 bytes).
Keywords: Georgia; Oral histories; Sound recordings; Hoboken (Ga.); Brantley County (Ga.); Sacred Harp; Gospel music; Primitive Baptists; Lee, David Irwin (1954-); Lee, Wilbur Clarke (1956-)